2013
DOI: 10.1136/bmj.f5432
|View full text |Cite|
|
Sign up to set email alerts
|

Aircraft noise and cardiovascular disease near Heathrow airport in London: small area study

Abstract: Objective To investigate the association of aircraft noise with risk of stroke, coronary heart disease, and cardiovascular disease in the general population.Design Small area study.Setting 12 London boroughs and nine districts west of London exposed to aircraft noise related to Heathrow airport in London.Population About 3.6 million residents living near Heathrow airport. Risks for hospital admissions were assessed in 12 110 census output areas (average population about 300 inhabitants) and risks for mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
176
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(184 citation statements)
references
References 30 publications
6
176
1
1
Order By: Relevance
“…[147][148][149] There is little data on population noise exposure other than in some highincome countries. 150 Such data, through measurement and modeling studies, are needed to quantify the burden of CVDs and other diseases attributable to noise.…”
Section: Other Environmental Risk Factorsmentioning
confidence: 99%
“…[147][148][149] There is little data on population noise exposure other than in some highincome countries. 150 Such data, through measurement and modeling studies, are needed to quantify the burden of CVDs and other diseases attributable to noise.…”
Section: Other Environmental Risk Factorsmentioning
confidence: 99%
“…Zusätzlich werden mehr indirekte Krankheitsindikatoren wie Medikamentenverbrauch und Inanspruchnahme des Gesundheitssystems erfasst [11,13]. In den letzten 20 Jahren wurden mehrere multinationale Projekte zu Verkehrslärm durchgeführt [7,9,16].…”
Section: Introductionunclassified
“…Current evidence linking aircraft noise to cardiovascular disease is generally interpreted as evidence of a chronic exposure effect (Babisch, 2006;Hansell et al, 2013;Correia et al, 2013;Floud et al, 2013;Jarup et al, 2008). Hansell et al found that people living near Heathrow airport and exposed to high levels of aircraft noise had increased rates of cardiovascular admissions and mortality .…”
Section: Discussionmentioning
confidence: 99%